The Influence of Organizational Commitment and Work Climate on the Performance of Higher Education Lecturers in Asahan District - Normansyah Normansyah; Yusniar Lubis; Yusuf Ronny Edward (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Many factors are considered capable of determining the quality of lecturer performance in tertiary institutions. Therefore, this study will test whether there is an effect of organizational commitment and work climate on the performance of university lecturers in Asahan district. Data collection In this study, economics was used with a focus on education management to test the factors of improving the quality of education with the intervening variable of teacher performance at tertiary institutions in Asahan District. This research was conducted in Asahan District which of the 14 tertiary institutions, one of which is Asahan University. The population in this study are university lecturers. This study uses a non-probability sampling method. The sample criteria in this study were that there were 115 permanent lecturers in tertiary institutions in the Asahan Regency. The results of the study show that organizational commitment has an influence on the quality of lecturer performance. Because with an organization that has a commitment to advancing the university, lecturers will be encouraged to participate. Likewise with the work climate which also has a very large influence on lecturer performance. This is due to a positive work climate and high morale. Then the lecturers will also have the enthusiasm to improve the reputation of the campus. So it was concluded that organizational commitment greatly influences the performance of lecturers in Asahan district.